Understanding human dopamine neuron biology in Parkinson's patient cells - Onal, Gizem; Caiazza, Maria Claudia; Sharifi, Parnaz; Thomas-Wright, Iona; Hoffmann, Johanna L.; Heon-Roberts, Rachel; Wade-Martins, Richard (Handbook of Behavioral Neuroscience, 2025)
Human-induced pluripotent stem cell (hiPSC) technology has revolutionized Parkinson's disease (PD) research, offering opportunities for disease modeling, drug discovery, and personalized medicine. In this chapter, we summarize the impact of hiPSC-derived dopamine neurons (DaNs) on understanding various aspects of PD. This includes exploring PD dopamine neuron biology within the context of voltage-gated calcium channels and electrophysiology, emphasizing the role of calcium channels in neuronal vulnerability and in regulating dopamine release. We address findings related to α-synuclein pathology, highlighting its aggregation, secretion, and intracellular interactions. We also look into the details of the main PD pathology-related organelles: lysosomes, mitochondria, and the endoplasmic reticulum (ER). Lysosomal pathology is investigated, encompassing GBA1-related PD phenotypes, pH regulation, lysosomal calcium channels, and autophagy. Mitochondrial dysfunction is summarized in terms of bioenergetics, α-synuclein/mitochondria interplay, and the mitophagy pathway. We examine ER-related pathology through ER stress and calcium regulation, and the ER-mitochondria contact sites are discussed as a pivotal link between mitochondria and the ER. Finally, we provide a summary of the integration of CRISPR technology into hiPSC-PD research, with a specific focus on its potential in target identification, drug discovery, and therapeutic interventions for dopamine neuron pathology.